361 Beef flavor chemistry and how it influences sensory perception - Legako, Jerrad F (J Anim Sci, 2020)
Flavor can be simply defined as the combination of taste and aroma. Taste refers to the five basic receptors: sweet, salty, sour, bitter, and umami. Flavor is the perception of chemical compounds reacting with receptors in the oral and nasal cavities (aroma) in combination with taste. For beef, flavor is considered a primary eating quality trait. Flavor is developed during cooking through a combination of numerous chemical reactions, principally the Maillard reaction and oxidation of lipids. Any factor which mediates precursor compounds to these reactions may influence flavor chemistry and final perceived flavor. For the Maillard reaction, water-soluble compounds, such as free-amino acids and sugars, are essential and allow for the development of characteristic beef flavors. Likewise, oxidation of lipids, to a degree, provides beef -species-specific flavor. However, too much oxidation contributes to off-flavor. Both pre- and post-harvest factors may influence beef flavor precursor content and composition prior to cooking. Beef finishing diet is well understood to influence fatty acid composition. Meanwhile, carcass grade and muscle type each influence fatty acids. During post-mortem aging, free-amino acids and other metabolites accumulate in response to proteolysis. Recent work indicates that packaging type and retail environment also influence flavor precursor compounds. Finally, the aforementioned flavor pathways, lipid oxidation and the Maillard reaction, are initiated and accelerated during cooking. Therefore, degree-of-doneness and cookery type greatly influence beef flavor chemistry. These examples briefly depict how beef flavor chemistry may be influenced by common production factors, retail settings, and consumer preparation of beef. The resulting beef flavor dictates consumer liking of beef. Therefore, understanding beef flavor chemistry is integral to maintaining or increasing consumer satisfaction with beef.